EFFECT OF OFF-FARM INCOME ON SMALLHOLDER COMMERCIALISATION: EVIDENCE FROM RURAL FARMERS IN RWANDA - Jalloh, Mamoud Abdul (Universitas Kuningan, 2023)
This paper examines the effect of off-farm income on smallholder commercialisation in rural Rwanda using the Households survey (EICV 4) data from the National Institute of Statistics, Rwanda. The logit model was used to determine the influence of off-farm income on the probability of rural smallholder farmers commercialisation. The study found that off-farm income positively and significantly affects smallholder commercialisation and hence, compensates for missing or imperfect credit markets. This indicates that farmers use earnings from off-farm sources for liquidity purpose and to invest in agricultural production to increase marketable surplus rather than to smooth out consumption. Thus, the policy implications are that expanding higher earning rural enterprises through financial support, capacity building and human capital investment are vital. This could also improve the returns to labour for off-farm work participating land-poor households and quickens the process of smallholder agricultural commercialisation in Rwanda.